External factors determining seasonal breeding in a subtropical population of the shore crab Pachygrapsus transversus (Gibbes, 1850) (Brachyura, Grapsidae) - Flores, Augusto A.V.; Negreiros-Fransozo, Maria Lucia [UNESP] (Taylor & Francis, 1998)
Monthly samples of the shore crab Pachygrapsus transversus from two distinct annual periods showed that ovigerous females are present throughout the Year in the population. However, the relative ovigerous abundance of specimens among sexually mature changes from less than 10% during the winter months to almost 80% in summer. Linear correlations for each year revealed that both temperature and photoperiod were positively associated with relative abundance of ovigerous females. Multiple regression analyses suggested that photoperiod was the main factor affecting breeding in this species. Timing of observed reproductive pattern may enhance larval survival because of particular oceanographic conditions in the study region and favor early juvenile development due to certain species-specific growth features.
Keywords: Environmental factors; Pachygrapsus transversus; Seasonal breeding; Shore crab